The edge of galaxy formation: II. Evolution of Milky Way satellite analogues after infall - Frings, Jonas; Buck, Tobias; Penzo, Camilla (Monthly notices of the Royal Astronomical Society, 2017)
Abstract. In the first paper, we presented 27 hydrodynamical cosmological simulations of galaxies with total masses between 5 × 108 and 1010 M⊙. In this second